(3HQeLI GdeRhOGJs - (3TdHGjI(B, (3eQGOs ((3YeGfs (3OGQ GdeSjQIs, 2002)
(3ebOeI Edi dZI (BPerl(3;CfhGY GdHjGfGJ aj dZI (BPerl(3,CfhGY GdeTZdGJ aj dZI (BPerl(3,Led GdTQW hGdOhQGf,eWGHbI GdCfeGW,GdbhGFe (BList(3,GdeUahaGJ GdGQJHGWjI,GdHQeLI GdaQYjI,GdedaGJ (BFiles(3,CSGSjGJ HQeLI (BCGI(3,GdGJUGd Hjf GdeJUaM hGdeRhO,GdfeGPL,JTajQ GdHjGfGJ,JWHjbGJ Gd(BCGIs
Keywords: (3GdHQeLI GdBdjIs; (3HQGeL GdMGSHGJs